2022
DOI: 10.1186/s43141-022-00327-2
|View full text |Cite
|
Sign up to set email alerts
|

Exploring genetic variation among Jordanian Solanum lycopersicon L. landraces and their performance under salt stress using SSR markers

Abstract: Background Tomatoes (Solanum lycopersicon L.) are one of the main daily consumed vegetables in the human diet. Tomato has been classified as moderately sensitive to salinity at most stages of plant development, including seed germination, seedling (vegetative), and reproduction phases. In this study, we evaluated the performance and response of 39 tomato landraces from Jordan under salt stress conditions. Furthermore, the landraces were also genetically characterized using simple sequence repea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 71 publications
3
19
0
Order By: Relevance
“…Ref. [ 45 ] obtained 100% of polymorphism for 4 SSR primers out of 5 for 39 Jordanian tomato landraces. Ref.…”
Section: Discussionmentioning
confidence: 99%
“…Ref. [ 45 ] obtained 100% of polymorphism for 4 SSR primers out of 5 for 39 Jordanian tomato landraces. Ref.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Yücel et al [49] observed that the fresh root weight, fresh shoot weight, dry root weight, and dry shoot weight decreased by screening nine chickpea genotypes under water limited conditions. Drought stress is significantly affected by the proline concentrations in the leaf tissue for tomato accessions [8]. A highly significant increment in proline content was detected at 40%FC compared to the control treatment (100% FC).…”
Section: Drought Tolerancementioning
confidence: 94%
“…It is known that tomato production is increased considerably worldwide [2][3][4][5]. In Jordan, a wide range of tomato cultivars and accessions were gathered from farmers and stored in the seed bank at the National Agricultural Research Center (NARC) [6][7][8]. In Jordan, the production of tomatoes increases year by year with high ability of export.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…SSR molecular marker technology involves tandem repeat sequence consisting of 1–6 nucleotides as repeat units, which has excellent characteristics such as co-dominant inheritance, high polymorphism, good reproducibility, and stable and accurate results. It has emerged as a key molecular marker technology for plant genetic diversity analysis, population structure research, variety identification, and molecular ID construction [ 4 , 5 , 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%